Influenza Virus Inactivated by Heavy Ion Beam Irradiation Stimulates Antigen-Specific Immune Responses - Kai Schulze; Ulrich Weber; Christoph Schuy; Marco Durante; Carlos Alberto Guzmán (MDPI AG, 2024)
The COVID-19 pandemic has made clear the need for effective and rapid vaccine development methods. Conventional inactivated virus vaccines, together with new technologies like vector and mRNA vaccines, were the first to be rolled out. However, the traditional methods used for virus inactivation can affect surface-exposed antigen, thereby reducing vaccine efficacy. Gamma rays have been used in the past to inactivate viruses. We recently proposed that high-energy heavy ions may be more suitable as an inactivation method because they increase the damage ratio between the viral nucleic acid and surface proteins. Here, we demonstrate that irradiation of the influenza virus using heavy ion beams constitutes a suitable method to develop effective vaccines, since immunization of mice by the intranasal route with the inactivated virus resulted in the stimulation of strong antigen-specific humoral and cellular immune responses.